Role of ocean in the genesis and annihilation of the core of the warm pool in the southeastern Arabian Sea - SHENOI, S. C.; SHANKAR, D.; GOPALAKRISHNA, V. V.; DURAND, F. (MAUSAM, 2005)
The earlier hypothesis, stated in the ARMEX (Arabian Sea Monsoon Experiment) Science Plan, that the ocean plays an important, but passive, role in the genesis of the core of warm pool in the southeastern Arabian Sea (SEAS) is examined in the light of new data collected during Phase II of ARMEX. The new evidence confirms that the ocean plays an important role. This paper summarises the results based on these data, which show that the remotely forced ocean dynamics plays an active, not passive, role not only in the genesis of the core of the warm pool in the SEAS, but also triggers the collapse of the warm pool.